2021
DOI: 10.1093/molehr/gaab067
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of uterine and placental ferroptosis by N-acetylcysteine in a rat model of polycystic ovary syndrome

Abstract: The mechanisms that link hyperandrogenism and insulin resistance to the increased miscarriage rate in women with polycystic ovary syndrome (PCOS) remain elusive. Previous studies demonstrate that increased uterine and placental ferroptosis is associated with oxidative stress-induced fetal loss in a pre-clinical PCOS-like rat model. Here, we investigated the efficacy and molecular mechanism of action of the antioxidant N-acetylcysteine (NAC) in reversing gravid uterine and placental ferroptosis in pregnant rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 84 publications
0
29
0
Order By: Relevance
“…Despite being commonly invoked as radical-trapping antioxidants, thiols are not competent in this regard. Their reactions with peroxyl radicals are not thermodynamically favorable (essentially thermoneutral), and the kinetics (<10 3 M –1 s –1 ) are too slow to compete with chain propagation, particularly given the low concentration and/or poor solubility of most thiols in lipid bilayers. , Nevertheless, increasing the availability of thiols, for example, via treatment with N -acetylcysteine (NAC), can have an impact on cellular lipid peroxidation and the cell’s resistance to ferroptosis. At first glance, the obvious mechanism would appear to be an increased pool of reduced glutathione, which serves as the reducing cosubstrate for the glutathione peroxidases (GPXs). However, it is plausible that other (GPX-independent) mechanism(s) contribute.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being commonly invoked as radical-trapping antioxidants, thiols are not competent in this regard. Their reactions with peroxyl radicals are not thermodynamically favorable (essentially thermoneutral), and the kinetics (<10 3 M –1 s –1 ) are too slow to compete with chain propagation, particularly given the low concentration and/or poor solubility of most thiols in lipid bilayers. , Nevertheless, increasing the availability of thiols, for example, via treatment with N -acetylcysteine (NAC), can have an impact on cellular lipid peroxidation and the cell’s resistance to ferroptosis. At first glance, the obvious mechanism would appear to be an increased pool of reduced glutathione, which serves as the reducing cosubstrate for the glutathione peroxidases (GPXs). However, it is plausible that other (GPX-independent) mechanism(s) contribute.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NAC possesses anticancer and anti-HIV, properties, further linking ELS to these pathologies ( Roederer et al, 1992 ; Deng et al, 2019 ). Moreover, as NAC supplementation increases GSH and GPX, it may also suppress ferroptosis and FIN ( Karuppagounder et al, 2018 ; Hu et al, 2021 ).…”
Section: N-acetylcysteinementioning
confidence: 99%
“…Of note, it was revealed by differential gene expression analysis that the interaction of autophagy, apoptosis, and ferroptosis contributed to the development of porcine ovarian atresia. 10 In addition, these ferroptosis inhibitors, Ferrostatin-1, 71 N-acetylcysteine, 72 Cryptotanshinone, 73 have shown that they can relieve symptoms in PCOS patients. Ferroptosis is generally considered to be intimately associated with the pathogenic alterations of PCOS, while the precise mechanism is still currently unclear.…”
Section: Pcosmentioning
confidence: 99%